Pengaruh Komposisi Serat Sisal Terhadap Konduktivitas Termal Dan Penyerapan Suara Papan Komposit - fatmawati hendrik fatma; Fauzi Widyawati (Fakultas Teknologi Lingkungan dan Mineral - Universitas Teknologi Sumbawa, 2024)
Thermal conductivity and sound absorption are two key characteristics in the development of innovativecomposite materials. Thermal conductivity reflects a material's ability to conduct heat from one place toanother, while sound absorption indicates a material's ability to absorb sound waves. Composite boardsare increasingly popular in various applications, especially in the furniture industry, as they creatematerials with superior properties compared to single materials used in their production. Previousresearch has identified the potential of natural fibers as reinforcement in composite boards due to theireco-friendly and biodegradable nature. However, research combining thermal conductivity and soundabsorption in composite boards with natural fibers is still limited. This study aims to explore the influenceof various compositions of sisal fibers on the thermal conductivity and sound absorption of compositeboards. Sisal fibers were chosen as the reinforcement due to their eco-friendly nature, low density, specific strength, and high modulus. The results show a significant increase in thermal conductivity ofcomposite boards at 10% to 30% volume fraction of sisal fibers. The uniform distribution of sisal fiberswithin the composite matrix and good fiber orientation enhance the heat transfer efficiency in thecomposite. Sound absorption testing reveals that composite boards with 30% volume fraction of sisalfibers have the highest sound absorption coefficient, 0.494 at 200 Hz, while those with 10% volumefraction have the lowest coefficient, 0.059 at 800 Hz. This study unveils the potential of sisal fibercomposite boards as an eco-friendly alternative material with good thermal conductivity and effectivesound absorption. The findings are expected to contribute to the development of high-performancecomposite materials for various applications, including construction and furniture. Further research isneeded to optimize the performance of this material and explore its potential in broader industrial andenvironmental contexts.